High selectivity of a novel D–A structured copolymer as a gas chromatographic stationary phase toward aromatic isomers. (11th May 2022) - He, Yongrui; Zheng, Bing; Qi, Meiling; Huo, Lijun
Abstract : This work reports a new π-conjugated copolymer with D–A structure (PBDB-T) as the stationary phase for gas chromatography (GC) with high resolving performance towards aromatic isomers of high similarity in structure and properties. Abstract : This work reports the separation performance of a new π-conjugated copolymer (PBDB-T) with alternating electron-donor and electron-acceptor units as the stationary phase for capillary gas chromatography (GC). To date, they have not been explored in the field of chromatography. The PBDB-T column exhibited a column efficiency of 3850 plates m −1 determined by n -dodecane at 120 °C and high-resolution performance toward a wide range of aromatic isomers, particularly halobenzenes, phenols, anthracene and phenanthrene. Moreover, it showed excellent separation repeatability and reproducibility in terms of run-to-run, day-to-day and column-to-column and good thermal stability. This work demonstrates the good potential of the indicated D–A copolymer as a new class of stationary phase for chromatographic analyses.